Evaluasi Pelayanan Kesehatan bagi Peserta BPJS di RSUD Madising Kabupaten Pinrang - Darwis, Umar; Usman, Usman; Wahyuni Sari, Rasidah; Muin, Herlina; Amir, Rahmi (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2026)
This study aims to evaluate the quality of healthcare services at RSUD Madising using the RATER model, which includes five key dimensions: responsiveness, assurance, tangibles, empathy, and reliability. Data were collected through interviews with informants who had direct experience with the hospital's services. The findings indicate that RSUD Madising has provided relatively good and responsive care in addressing patients’ needs. The readiness of medical personnel, especially nurses, and the use of empathetic communication are among the main strengths observed. Despite challenges such as limited staff, particularly during night shifts, the hospital maintains service quality through regular supervision, well-maintained medical facilities, and a clean, comfortable environment. Furthermore, the hospital’s humane approach to emergency patients and inclusive policies for underprivileged individuals reflect its commitment to equity and patient safety. The evaluation of administrative procedures and the active involvement of patients through satisfaction surveys further support a responsive and accountable healthcare system. This study concludes that optimal service quality is not solely determined by technical competence, but also by humanistic values, effective communication, and sound service management.